Identification of delta/notch-like epidermal growth factor-related receptor as the Tr antigen in paraneoplastic cerebellar degeneration - de Graaff, Esther; Maat, Peter; Hulsenboom, Esther; van den Berg, Robert; van den Bent, Martin; Demmers, Jeroen; Lugtenburg, Pieternella J.; Hoogenraad, Casper C.; Sillevis Smitt, Peter (Annals of neurology, 2012)
Objective: Anti‐Tr is among the better described autoantibodies in paraneoplastic cerebellar degeneration (PCD) combined with Hodgkin lymphoma (HL); however, the Tr antigen remains unidentified. Methods: We used immunoprecipitation of total rat brain extract followed by mass spectrometry to identify the antigen recognized by anti‐Tr–positive sera. By Western blotting and cell‐based assays, we tested a total of 12 anti‐Tr–positive and 246 control sera and determined the region of the epitope recognized by the anti‐Tr antibodies. Deletion and mutant constructs were generated to further map the antigenic region. Results: Mass spectrometry analysis of immunopurified rat brain extract using 4 different anti‐Tr–positive sera led to the identification of Delta/Notch‐like epidermal growth factor‐related receptor (DNER) as the Tr antigen. All but 1 of 246 control samples were negative in the HeLa cell‐based screening assay, whereas 12 of the 12 anti‐Tr–positive sera stained hemagglutinin‐tagged DNER‐expressing cells. Only 1 control subject with HL but no ataxia was found to be both DNER and Tr positive. Using deletion constructs, we pinpointed the main epitope to the extracellular domain. Knockdown of endogenous DNER in hippocampal and N‐glycosylation mutations abolished the anti‐Tr staining, indicating that glycosylation of DNER is required for it to be recognized by anti‐Tr antibodies. Interpretation: DNER is the antigen detected by anti‐Tr–positive sera. Presence of anti‐Tr antibodies in patients with PCD and HL or HL only can now be screened quickly and reliably by using a cell‐based screening assay. ANN NEUROL 2012